Aquaporin-3 is down-regulated in jejunum villi epithelial cells during enterotoxigenic Escherichia coli-induced diarrhea in mice. (June 2017) - Zhang, Di; Zhang, Kaiqi; Su, Weiheng; Zhao, Yuan; Ma, Xin; Qian, Gong; Qu, Guijuan; Pei, Zhihua; Liu, Shuming; Ma, Hongxia
Abstract: Enterotoxigenic Escherichia coli (ETEC)-induced diarrhea is a complex pathological process, involving ion channel regulation and water efflux. While the mechanism underlying water efflux in ETEC-induced diarrhea is still largely unknown, aquaporins (AQPs) play important roles in transcellular water movement, but their expression profile has not been demonstrated in the murine small intestine. We identified AQP3 expression in the jejunum, but not the duodenum or ileum, using reverse transcription PCR and western blotting. Immunohistochemistry showed that AQP3 localized to the jejunum villi epithelial cells. Using an ETEC-induced murine diarrhea model, we demonstrated that both AQP3 mRNA expression and protein concentration in the jejunum were gradually but significantly decreased over 7 d compared with controls. These results suggested impaired water influx also plays an important role in ETEC-induced diarrhea. Highlights: Aquaporin-3 expressed and located in jejunum villi epithelial cells of the mice. Aquaporin-3 is down-regulated during ETEC-induced diarrhea in mice.